Image and video retrieval 4th international conference, CIVR 2005, Singapore, July 20-22, 2005 ; proceedings - CIVR (Information systems and applications, incl. internet/web, and HCI, 2005)
It was our great pleasure to host the 4th International Conference on Image and Video Retrieval (CIVR) at the National University of Singapore on 20–22 July 2005. CIVR aims to provide an international forum for the discussion of research challenges and exchange of ideas among researchers and practitioners in image/video retrieval technologies. It addresses innovative research in the broad field of image and video retrieval. A unique feature of this conference is the high level of participation by researchers from both academia and industry. Another unique feature of CIVR this year was in its format – it ofered both the traditional oral presentation sessions, as well as the short presentation cum poster sessions. The latter provided an informal alternative forum for animated discussions and exchanges of ideas among the participants. We are pleased to note that interest in CIVR has grown over the years. The number of submissions has steadily increased from 82 in 2002, to 119 in 2003, and 125 in 2004. This year, we received 128 submissions from the international communities: with 81 (63.3%) from Asia and Australia, 25 (19.5%) from Europe, and 22 (17.2%) from North America. After a rigorous review process, 20 papers were accepted for oral presentations, and 42 papers were accepted for poster presentations. In addition to the accepted submitted papers, the program also included 4 invited papers, 1 keynote industrial paper, and 4 invited industrial papers. Altogether, we ofered a diverse and interesting program, addressing the current interests and future trends in this area. Invited presentations - Lessons for the future from a decade of informedia video analysis research - Large scale evaluations of multimedia information retrieval: the TRECVid experience - Image and video retrieval from a user-centered mobile multimedia perspective - Multimedia research challenges for industry - Industrial presentations - Practical applications of multimedia search - Video story segmentation and its application to personal video recorders - High-speed dialog detection for automatic segmentation of recorded TV program - Intellectual property management & protection and digital right management in MPEG - Towards media semantics: an I2R perspective - Video retrieval techniques - A comparison of score, rank and probability-based fusion methods for video shot retrieval - EMD-based video clip retrieval by many-to-many matching - Video story segmentation and event detection - Visual cue cluster construction via information bottleneck principle and kernel density estimation - Story segmentation in news videos using visual and text cues - boundary error analysis and categorization in the TRECVID news story segmentation task - Semantic event detection in structured video using hybrid HMM/SVM - Semantics in video retrieval - What can expressive semantics tell: retrieval model for a flash-movie search engine - The use and utility of high-level semantic features in video retrieval - Image indexing and retrieval - Efficient shape indexing using an information theoretic representation - Efficient compressed domain target image search and retrieval - An effective multi-dimensional index strategy for cluster architectures - Image/video annotation and clustering - Systematic evaluation of machine translation methods for image and video annotation - Automatic image semantic annotation based on image-keyword document model - Region-based image clustering and retrieval using multiple instance learning...